Preferences for One-Shot Resolution of Uncertainty and Allais-Type Behavior - Dillenberger, David (Econometrica, 2010)
Experimental evidence suggests that individuals are more risk averse when they perceive risk gradually.We address these …ndings by studying a decision maker (DM) who has recursive preferences over compound lotteries and who cares about the way uncertainty is resolved over time.DM has preferences for one-shot resolution of uncertainty (PORU) if he always prefers any compound lottery to be resolved in a single stage.We establish an equivalence between dynamic PORU and static preferences that are identi…ed with the behavior observed in Allais-type experiments.The implications of this equivalence on preferences over information systems are examined.We de…ne the gradual resolution premium and demonstrate its magnifying e¤ect when combined with the usual risk premium.In an intertemporal context, PORU captures "loss aversion with narrow framing".